The petrogenesis and emplacement of Proterozoic dyke swarms in Labrador. - Andrew Christopher. Cadman (1992)
The Archaean Hopedale Block, in the southern Nain Province of Labrador, Canada, is host to three generations of mafic intrusions of Proterozoic age; the 2.2 Ga Kikkertavak, the 1.6 Ga Kokkorvik and the 1.3 Ga Harp dyke swarms. Also present are two ultrabasic dyke types: firstly pyroxenites interpreted as coeval with the Kikkertavak swarm, and secondly 'high titanium dykes' with opaque-rich compositions of uncertain age. Many Kikkertavak (and Harp) intrusions show highly differentiated phyric textures attributed to rhythmic changes in flow conditions during solidification. Modelling of intradyke geochemical variation shows this can be largely correlated with phenocryst differentiation processes. Other textures indicate more extreme flow variations associated with composite intrusion. Analysis of Kikkertavak dyke morphologies and measurements of magma palaeo-flow directions using anisotropy of magnetic susceptibility suggests that the crack propagation direction during dyke emplacement may be decoupled from the preserved flow direction. However similar measurements on the Kokkorvik sheets suggests that decoupling does not occur in shallow-angle intrusions. Approaching the southern boundary of the Hopedale Block, Kikkertavak dykes show increasing tectonic, petrographic and geochemical alteration. The principle effects are mobile element depletion and redistribution, notably on the dyke margins. Fractional crystallisation, crustal contamination and partial melting processes alone are inadequate at explaining primary geochemical variation in both Kikkertavak and Harp swarms. Instead variation occurs mainly due to the melting of heterogeneous mantle sources. The iron-rich compositions of many Kikkertavak dykes is postulated to result from the underplating into the subcontinental mantle during subduction of mafic ocean plateau material. The geochemical signature of many Harp dykes may result from mixing with similar iron-rich mantle sources with alkaline partial melts added to the continental lithosphere. The ...